It's Not Easy Being Green: The Role of Self-Evaluations in Explaining Support of Environmental Issues - Sonenshein, Scott; DeCelles, Katherine A.; Dutton, Jane E. (Academy of Management Journal, 2014)
Using a mixed methods design, we examine the role of self-evaluations in influencing support for environmental issues. In Study 1—an inductive, qualitative study—we develop theory about how environmental issue supporters evaluate themselves in a mixed fashion, positively around having assets (self-assets) and negatively around questioning their performance (self-doubts). We explain how these ongoing self-evaluations, which we label “situated self-work,” are shaped by cognitive, relational, and organizational challenges individuals interpret about an issue from a variety of life domains (work, home, or school). In Study 2—an inductive, quantitative, observational study—we derive three profiles of environmental issue supporters' mixed selves (self-affirmers, self-critics, and self-equivocators) and relate these profiles to real issue-supportive behaviors. We empirically validate key constructs from Study 1 and show that even among the most dedicated issue supporters, doubts play an important role in their experiences and may be either enabling or damaging, depending on the composition of their mixed selves. Our research offers a richer view of both how contexts shape social issue support and how individuals' self-evaluations play a meaningful role in understanding the experiences and, ultimately, the issue-supportive behaviors of individuals working on social issues.